IMPLEMENTASI FUNGSI LEGISLASI DAN PENGAWASAN DPRD (STUDI KASUS DPRD KABUPATEN MAMASA PERIODE 2014-2019) - Niko Niko; Agustinus Sudi (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2019)
This study aims to determine the implementation of the legislative and supervisory functions of the Mamasa District Representative Council for the 2014-2019 period related to the implementation and solution. The study is descriptive qualitative with a case study approach. The research method uses interview, observation and documentation. The results of this study indicate that the legislative function which is the direction of motion and performance achievements in terms of stipulating regional regulations that have been determined is still not subject to all formulations in terms of regional empowerment. In the case of the implementation of the supervisory function, even though the DPRD has carried out its utmost in accordance with the mechanism, but in the community's evaluation, the supervisory function has not been running well.